Implementasi Project Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan lil Alamin ( P2RA) di Madrasah - Susanti, Fitri; Kusen; Sumarto (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Pancasila character education in Indonesia is an integral part of the formation of quality and ethical student character. MTsN 01 Kepahiang is an educational institution that is active in implementing the values of Pancasila by integrating Islamic values and local culture. The character of Pancasila to graduates has a crucial role. This study aims to explore and describe how the implementation of the student profile project who have undergone Pancasila character learning by integrating Islamic values in MTsN 01 Kepahiang. The methods used were participatory observation, researchers actively participatory in daily school activities, and in-depth interviews with several graduates to explore their understanding of the values of Pancasila and the impact of its application every day. The results explained that MTsN 01 Kepahiang students have a deep and varied understanding of the value of Pancasila, able to explain the meaning and relevance of these values in various aspects of their lives. The observations show that graduate behaviour reflects the application of Pancasila values in social interaction, personal decisions, and participation in society. The discussion raised important implications for character education in MTsN 1 Kepahiang, affirmed the success of the applied in Pancasila character and the need to improve teaching methods and collaboration with various related parties to strengthen the positive impact of Pancasila character education Rahmatan lil Alamin at MTsN 01 Kepahiang.